Pengembangan Perangkat Pembelajaran Berbasis Budaya Banten Pada Tema 5 di Kelas 5 Sekolah Dasar - Syafani, Nabilla; Wuryastuti, Sri (Didaktika, 2022)
Cultural preservation is an anticipation of the impact of globalization through various aspects that need to be developed. One aspect that can develop cultural identity as a means of preserving culture, especially in the younger generation, is through education. Culture-based learning brings local culture which has not had a place in the school curriculum, including in the learning process of various subjects at school. This research aims to develop and determine the feasibility of Banten culture-based learning tools for theme 5 in fifth-grade elementary schools. The research method used is RD and was developed using the ADDIE model. The learning tools developed include Lesson Plan, Students Worksheet, teaching materials and test questions. The learning tools developed were validated by material experts and evaluation experts. This learning device was tested on 15 students at the State Elementary School of Buah Gede. Data collection techniques in this research are observation and interviews. The results of this development research are that based on the results of the implementation of the lesson plans with positive and relatively good student responses, the learning tools can be used in learning activities, the learning tools are suitable for use by considering aspects such as good language according to enhanced spelling, perfected spelling or improved spelling, without ambiguity and adapting to age. respondents and content that is relevant to the content standards in the curriculum. Based on the research results, the learning design developed is suitable for use in learning on theme 5 in fifth grade in elementary schools.